THE PARADOX OF PROSPERITY: KNOWLEDGE-BASED GROWTH AND YOUTH UNEMPLOYMENT IN INDONESIA - A SYSTEMATIC REVIEW - Sabarno Dwirianto; Atika Ananda Sabrina; Martin; Rendika Adisman; Mulia Sosiady (DIVERSITY Logic Journal Multidisciplinary, 2026)
Background. Millions of educated young people in Indonesia remain unable to secure decent employment despite optimistic national economic growth figures, a paradox that motivates this study. Research purpose. This study pursues four interrelated objectives: (1) to systematically map the relationship between knowledge-based economic growth and youth unemployment as documented in the global academic literature; (2) to identify determinants of youth unemployment that remain consistent across diverse country contexts; (3) to analyze the developmental consequences of persistently high youth unemployment for Indonesia; and (4) to identify the research gaps that must be addressed to support evidence-based policymaking. Research method. Guided by the PRISMA 2020 framework, this systematic literature review analyzes 401 Scopus-indexed publications identified through four structured search strategies conducted in April 2026. The retrieved studies were synthesized through three sequential stages: descriptive analysis of publication trends and methodological orientations, thematic analysis coding recurring constructs into clusters, and critical synthesis integrating themes while surfacing contested findings and gaps. Findings. The results indicate that economic expansion does not automatically generate youth employment, as absorptive capacity depends on sectoral composition. Youth unemployment in Indonesia stems primarily from coordination failures across education, labor institutions, and policy rather than from skill deficits alone. Its consequences extend beyond statistical indicators, suppressing GDP growth, threatening social stability, and producing scarring effects on human capital, while underutilized opportunities remain in community-based entrepreneurship, industry education partnerships, and green–blue economy development. Conclusion. This study advocates a shift from fragmented interventions toward an integrated, evidence-driven youth employment policy framework.